Exchange rate fluctuations and the margins of exports - Richard Fabling; Lynda Sanderson (New Zealand Government, The Treasury, 2015)
This paper examines the relationship between exchange rate fluctuations and New Zealand export performance. To isolate the impact of the exchange rate, as opposed to contemporaneous (and related) fluctuations in New Zealand's economic performance or overseas market characteristics, we focus on bilateral export relationships at the firm level and control for both time-invariant country characteristics and changes in aggregate economic conditions. We examine two key margins of export adjustment – the probability of exporting (the extensive margin) and the average value of exports per firm (the intensive margin) – and distinguish between impacts on market incumbents and new or potential entrants. Finally, we specifically take account of the potential for interaction between the level and volatility of the exchange rate to affect exporting, as implied by theories of exchange rate hysteresis.
Keywords: D22; F14; F31; 330; Wechselkurs; Handelseffekt; Hysterese; Neuseeland